2020
DOI: 10.1073/pnas.1920582117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of a host protein by NS1 of pandemic and seasonal influenza A viruses

Abstract: The 1918 influenza A virus (IAV) caused the most severe flu pandemic in recorded human history. Nonstructural protein 1 (NS1) is an important virulence factor of the 1918 IAV. NS1 antagonizes host defense mechanisms through interactions with multiple host factors. One pathway by which NS1 increases virulence is through the activation of phosphoinositide 3-kinase (PI3K) by binding to its p85β subunit. Here we present the mechanism underlying the molecular recognition of the p85β subunit by 1918 NS1. Using X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 68 publications
4
49
0
Order By: Relevance
“…Here, we characterize the binary and ternary interactions mediated by 1918 NS1 using a combination of biophysical approaches, including biolayer interferometry (BLI) and nuclear magnetic resonance (NMR). Our laboratory recently determined the crystal structure of 1918 NS1 complexed with the p85 subunit [27]. In the present study, we find that 1918 NS1 complexed with p85 hijacks CRK through a fuzzy electrostatic interaction mediated by its CTT.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…Here, we characterize the binary and ternary interactions mediated by 1918 NS1 using a combination of biophysical approaches, including biolayer interferometry (BLI) and nuclear magnetic resonance (NMR). Our laboratory recently determined the crystal structure of 1918 NS1 complexed with the p85 subunit [27]. In the present study, we find that 1918 NS1 complexed with p85 hijacks CRK through a fuzzy electrostatic interaction mediated by its CTT.…”
Section: Introductionsupporting
confidence: 57%
“…For example, Jureka et al showed that the RBD of 1918 NS1 directly interacts with the RIG-I CARD domain while the interaction was not observed for the protein from the Udorn strain [25]. Moreover, our laboratory revealed that the ED of 1918 NS1 (1918 NS1 ED ) binds to p85 iSH2 with drastically different binding characteristics to those from the ED of the Udorn strain [27].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations